Green Investment Strategies in Sustainable Islamic Economics: A Viable Solution for Global Recession Challenges - Syaichoni , Ahmad (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2020)
The main objective of this study is to analyze the potential of green investment strategies in the context of the Islamic economy as a sustainable and viable solution to face the challenges of the global recession. The research methods used include an in-depth literature review of Islamic economic concepts, the principles of green investment, and their impact on the environment and economy. The study also involves an analysis of green investment instruments that conform to Islamic economic principles, such as green sukuk and investment in renewable energy. The data and information collected are analyzed qualitatively to understand the implications of implementing green investment strategies in the context of Islamic economics. The results of this study show that green investment strategies in the Islamic economy have great potential to generate positive impacts on the environment and economy. Islamic economics can promote sustainability, social justice, and environmental responsibility by using green investment instruments such as green sukuk and investment in renewable energy. In addition, the implementation of green investment strategies in the Islamic economy can also be a sustainable solution to overcome the challenges of the global recession.